Economical Design of Sewer Line in Flat Terrain: A Case Study of Rajapur Sewerage System - Ojha, Bibhuti (SCITECH Nepal, 2018)
Design of sewer line in flat terrain is a great challenge due to high excavation depth involved in laying a sewer line required for maintaining minimum velocity, slope and clear cover. Sewer design presented in this paper is result of sewer modelling software Bentley SewerCAD V8i. Estimation and cost analysis of a sewer system shows cost is directly related to the excavation depth. For economically efficient design of sewer line in a flat terrain of Rajapur-Bardia, sewer is designed in the gentle slope and flushing tanks are provided at sections where velocities are less than the minimum value recommended by Codes. Design and cost estimation of sewer network of 4.554 km with and without use of flushing tank are presented in this paper and two major benefits - cost and low invert level of outfall from ground surface elevation are achieved with flushing tank provision.